11(m-6)=-3(m-6)

Simple and best practice solution for 11(m-6)=-3(m-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(m-6)=-3(m-6) equation:


Simplifying
11(m + -6) = -3(m + -6)

Reorder the terms:
11(-6 + m) = -3(m + -6)
(-6 * 11 + m * 11) = -3(m + -6)
(-66 + 11m) = -3(m + -6)

Reorder the terms:
-66 + 11m = -3(-6 + m)
-66 + 11m = (-6 * -3 + m * -3)
-66 + 11m = (18 + -3m)

Solving
-66 + 11m = 18 + -3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '3m' to each side of the equation.
-66 + 11m + 3m = 18 + -3m + 3m

Combine like terms: 11m + 3m = 14m
-66 + 14m = 18 + -3m + 3m

Combine like terms: -3m + 3m = 0
-66 + 14m = 18 + 0
-66 + 14m = 18

Add '66' to each side of the equation.
-66 + 66 + 14m = 18 + 66

Combine like terms: -66 + 66 = 0
0 + 14m = 18 + 66
14m = 18 + 66

Combine like terms: 18 + 66 = 84
14m = 84

Divide each side by '14'.
m = 6

Simplifying
m = 6

See similar equations:

| -45+2x=-6x+51 | | -15+4x=9 | | 5(6x+4)=30x+20 | | 6(x-2)=4x-6 | | 6m-3=77 | | 540/90=x/90 | | -4+x+1=5x-7 | | 540/90 | | .065(x-2000)=.04x+70 | | -26.34-42.18=x | | (3x+1)/2=x+7 | | x+(5/8)=2x-(5/8) | | 27=13+x | | 12=.75x | | -16+2x+3x^2=0 | | (8b+3)(6b+7)=0 | | 8200+3/92x=3/33x | | 32x^2=16x | | x*48=2928 | | -12-6=x | | 8p+3+5=-6(2p-8)+10(p-10) | | 6x+12x-81=9 | | 6y=46 | | 5(2x-1)+(1+x)=37 | | 8*x=16 | | (3x-48)=156 | | 8(8n-6)=-8(9n+6) | | 2(x+3)-3x=5 | | y+23=-2x+6 | | 5x-6y=-32 | | -2x+x+2x+5=-3 | | x+12=-2x+6 |

Equations solver categories